Preparation and properties of Nanoporous Hydroxiapatite Cement using Polyurethane - Sariah Saalah; Coswald Stephen Sipaut @ Mohd Nasri; Murni Sundang (Universiti Malaysia Sabah, 2013)
This research examines optimum sized polyurethane foam (PUF) as a mould for the formation of porous hydroxyapatite, HAp (Calcium Phosphate Cement-base). Four PUFs of different formulations were selected based on their cell size and the percentage of open cell structure. In the preparation of porous HAp, tetracalcium phosphate (TTCP) and dicalcium phosphate anhydrous (OCPA) were mixed at a molar ratio of 1:1 in the presence of a cement setting solution namely, sodium phosphate. The effects of the morphology and the cell size of PUF on HAp morphology were analyzed with a scanning electron microscope(SEM). Based on the analysis, it was observed that only PUFs with an average cell size of approximately 600 µm and with a 95 % open cell structure could optimally generate porous HAp. This porous HAp fulfils the two criteria for an ideal porous implant which include a cell size of more than 100 µm with a high percentage of open cell content (> 50 %) and free from PUF mould residue. However, the porous Hap obtained had a low compressive strength of 0.47 ± 0.056 MPa.